New concepts in the treatment of dermal lesions caused by Hansen's disease (Leprosy) - Bermudez Cedeño, Gonzalo A. (Revista Universidad de Guayaquil, 1985)
Man is curious by nature, and in his desire to discover and investigate he has managed to provide humanity with all the advances currently available to modern science.